Two new species of Stenoloba Staudinger, 1892 and one Victrix Staudinger, 1879 from East Asia and China (Lepidoptera, Noctuidae, Bryophlilinae) - Han, Hui Lin; Kononenko, Vladimir S. (Zootaxa, 2021)
Two new species of the genus Stenoloba Staudinger, 1892 (S. mediana, sp. n. and S. fuscobrunnea, sp. n.) are described from Cambodia and Laos respectively, and a new species of the genus Victrix Staudinger, 1879 (V. noloides, sp. n.) from China is described. Stenoloba chlorographa Kononenko & Ronkay, 2001 is reported for the first time from China (Xizang), and new distributional data for recently described Stenoloba species from Malaysia are presented.